If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -55 = -8n + 9 Reorder the terms: -55 = 9 + -8n Solving -55 = 9 + -8n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '8n' to each side of the equation. -55 + 8n = 9 + -8n + 8n Combine like terms: -8n + 8n = 0 -55 + 8n = 9 + 0 -55 + 8n = 9 Add '55' to each side of the equation. -55 + 55 + 8n = 9 + 55 Combine like terms: -55 + 55 = 0 0 + 8n = 9 + 55 8n = 9 + 55 Combine like terms: 9 + 55 = 64 8n = 64 Divide each side by '8'. n = 8 Simplifying n = 8
| 6x+34=16x-66 | | 3x+2y=z+50 | | -92+w=-10 | | -12=y-36 | | -10a=-72 | | 10x+5=4x+41 | | m-(-4)=32 | | 8=6x-4 | | 2x^2-2=-5x-3 | | -8e=4 | | K+(-50)=-100 | | 45p=-180 | | x+10=3*x*x-1*1 | | 13+-1= | | X+4=3x+4 | | 87-2x=4x+21 | | 7+-6= | | 5n^2+4n-1=0 | | 79-4x=10+23 | | 3+5x=27+x | | 5x-4=12x-53 | | 4x+16=14x-84 | | 12x-27=8x+1 | | 10x+8=7x+29 | | 6(2x-5)-2x-4x=6 | | 6(2x-5)-2-4=6 | | 2x+1=3x-9 | | r^2=16 | | s^2+6s=16 | | 9t^2+36t-108=0 | | b^2-4b-32=0 | | 2m-6=12+4 |